2017
DOI: 10.1159/000484603
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Residual Renal Function with Cardiovascular Morbidity in Hemodialysis Patients and the Potential Role of Monocyte Chemoattractant Protein-1

Abstract: Background: Residual renal function (RRF) provides several benefits to patients on dialysis. Monocyte chemoattractant protein-1 (MCP-1) plays an important role in atherosclerotic lesions. We considered the relationship between RRF and cardiovascular morbidity and the significant role of MCP-1 serum concentrations in hemodiafiltration (HDF) patients. Methods: We enrolled 76 patients on on-line HDF. RRF was defined by interdialytic urine output, and we studied the patients in two groups according to the preserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
4
6
1
Order By: Relevance
“…The fact that only HFD effectively clears active MMP-9 might suggest that HFD is more efficient than OL-HDF; however, pre-dialysis active MMP-9 was significantly lower in the OL-HDF group than in HFD patients, indicating that the levels of active MMP-9 are better controlled in patients under OL-HDF. Moreover, residual renal function is associated with lower inflammation in OL-HDF [37,38]. Supporting this, we also observed that active MMP-9 is lower in patients with greater interdialytic urine volume, which is superior to eGFR as an estimate of residual renal function in dialysis [28].…”
Section: Discussionsupporting
confidence: 81%
“…The fact that only HFD effectively clears active MMP-9 might suggest that HFD is more efficient than OL-HDF; however, pre-dialysis active MMP-9 was significantly lower in the OL-HDF group than in HFD patients, indicating that the levels of active MMP-9 are better controlled in patients under OL-HDF. Moreover, residual renal function is associated with lower inflammation in OL-HDF [37,38]. Supporting this, we also observed that active MMP-9 is lower in patients with greater interdialytic urine volume, which is superior to eGFR as an estimate of residual renal function in dialysis [28].…”
Section: Discussionsupporting
confidence: 81%
“…However, it has been suggested that mediators other than endothelin-1 may be responsible for increased intradialytic vascular resistance [ 9 ]. Our recent previous study showed that the loss of residual renal function related to fluid overload was associated with cardiovascular outcomes in dialysis patients, due additionally to the coexistence of increased levels of monocyte chemoattractant protein-1 (MCP-1), a chemokine, which may reflect a progressive inflammation/oxidative stress condition [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness was measured as carotid-femoral pulse wave velocity (c-fPWV) and carotid augmentation index (AIx) using the SphygmoCor System® (AtCor Medical Pty. Ltd., Sydney, Australia) according to the manufacturer's specifications [ 14 ]. In each subject, two sequences of measurements were performed, and their mean was used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Raikou VD showed the similar significant higher level of diastolic dysfunction, LVH but non-significant higher level of systolic dysfunction between without preserved RRF and preserved RRFgroup. [14][15][16][17] Mean age was similar in the two group (43.22±16.93 vs 41.95±15.35, p=0.74). Highest of patients were in age group <30 years and ˃60 years.…”
Section: Discussionmentioning
confidence: 79%